Permodelan Banjir dan Strategi Mitigasi Bencana di Kelurahan Rapak Dalam - Caroline Pitaloka, Febi Ayu; Rahmat Aris, Pratomo (SPECTA Journal of Technology, 2024)
Flood disasters, stemming from both natural and human factors, present a significant threat to communities. Consider the case of Rapak Dalam Subdistrict in Samarinda City, where rapid development and improper land use have led to devastating flooding. The transformation of natural landscapes into residential areas, along with land excavation and mining, has disrupted the area's natural functions, resulting in increased runoff. In addition to human factors, natural elements such as rainfall and the lowland topography contribute to the frequent flooding. In 2018, a major flood forced around 10,000 people to evacuate due to prolonged rainfall, highlighting the urgent need for effective mitigation strategies. The overburdened Rapak Dalam Watershed was unable to contain the runoff, resulting in widespread devastation. Despite less intense rainfall, the frequency of flood incidents has risen, making it crucial to address these issues amidst ongoing land-use changes. To combat these challenges, hydrological modeling is essential in predicting and managing flood events caused by land-use changes. By calculating flood discharge, this approach enables the development of optimal mitigation strategies. It is imperative to take decisive action in the face of these escalating flood risks to safeguard communities and ensure sustainable development.